THE EFFECTIVENESS OF DIFFERENTIATED LEARNING FROM THE PERSPECTIVE OF CAROL ANN TOMLINSON IN THE LEARNING PROCESS OF ISLAMIC RELIGIOUS EDUCATION IN JUNIOR HIGH SCHOOL - Dhelta Big Queen Bulqis; Muhammad Zuhdi; Syamsul Aripin (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the effectiveness of differentiated learning in the subject of Islamic Religious Education and Ethics in the Independent Curriculum at SMP Muhammadiyah 1 Jakarta. This study uses mixed methods with a concurrent embedded model, where the qualitative approach is the main method and is strengthened by descriptive quantitative data. The analytical framework refers to Carol Ann Tomlinson's theory which includes three main pillars: philosophy, principles, and practice. The results of the study show that differentiated learning has been implemented effectively starting from the planning, implementation, to evaluation stages. PAI teachers actively adjust learning strategies based on the results of diagnostic assessments that identify students' readiness, interests, and learning styles. In the process, various learning methods such as discussions, worship practices, visual media, and content-based creative projects are used. The effectiveness of differentiated learning is also reinforced by quantitative data showing a significant improvement in the distribution of student grades. Prior to the implementation of differentiated learning (semester 1), most student scores were centered in the range of 85–87, with a mode and median score of 86, and only 3.3% of students reached the highest score range (88–90). After the implementation in semester 2, as many as 26.7% of students reached the score range of 91–93, with an increase in the mode and median to 91. This shows a shift in academic performance collectively towards a higher level. Students respond positively to this approach; They feel cared for, motivated, and more confident in following learning. Thus, these findings show that the implementation of differentiated learning in schools has proven to be effective in meeting the learning needs of students optimally in the learning process of Islamic Religious Education and Ethics.